السياسة الأمريكية تجاه قضايا التدخل في حقوق الإنسان - صيوح, لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
شهد العالم في السنوات الأخيرة عدة تحولات سياسية واقتصادية وأيديولوجية وعسكرية. وبرز وضع دولي جديد أثّر على العلاقات الدولية، وخصوصاً في طريقة معالجة مختلف المشاكل والقضايا المطروحة. كما أثر على تطبيق المبادئ التي يقوم عليها القانون الدولي، كمبدأ سيادة الدول والمساواة في السيادة ومبدأ حقوق الإنسان، ومبدأ عدم التدخل في الشؤون الداخلية للدول وغيرها من المبادئ. وتبعاً لهذه الوضعية تمَّ تشكل الخارطة العالمية مع بروز قطب سياسي واقتصادي وحيد، ففقد العالم بذلك توازنه الاستراتيجي، وسيطرت على العلاقات الدولية النزعة الأحادية التي برزت بالخصوص في مجال أخذ القرار العالمي، ومعالجة مختلف القضايا والمشاكل المطروحة في العالم، مما أدى إلى المساس بدور الأمم المتحدة، وبقية المنظمات الدولية الحكومية، وغير الحكومية التي تجمع منظمات حقوق الإنسان على اعتبار أن ما جرى في العراق ويجري في ليبيا كارثة إنسانية بكل المقاييس، من خلال التجاوزات التي ارتكبتها وترتكبها الولايات المتحدة من خلال القفز على الشرعية الدولية واختلاق مبررات غير واقعية لشن الحروب والعمليات العسكرية، وما تشهده من انتهاكات خطيرة لحقوق الإنسان المعترف بها دولياً من خلال معاهدات دولية تعدّ الولايات المتحدة الأمريكية طرفاً في أغلبها. In the last few years the world faced many political, economical, ideological and military changes, leading to the emergence of a new international situation. These changes had their effects on the international relations especially in the method of dealing with different issues and problems. They also affected on applying the principles on which the international law is based such as sovereignty, equality in sovereignty, the principles of human rights and the principle of not interfering in the internal affairs of other countries. On these bases a new international map is formed with the emergence of one political and economical pole. As a consequence, the world has lost its strategic balance and the one-pole trend has dominated the international relations and has manifested itself in the international decision-making and the current world issues. This, in turn, has compromised the role of the United Nations and other international government and non-government organizations that comprise the human rights organizations on the bases that what happened in Iraq and happening in Libya are considered a human disaster in all measures. Through the trespasses that the United States has committed, and still committing, by jumping over the international legitimacy and the contradictions in the unrealistic justifications for waging wars and military actions and the consequent violations of internationally admitted human rights through international treaties, for all these, the United States is considered part of most of them.